A proposal of rock dust, biological fixation of nitrogen and cooperatives based on Communities of Practice to reduce dependence on chemical fertilizers in Myanmar - De Angelis, Cristia (Journal of Economic Development, Environment and People, 2024)
The defense mechanism against the Coup in Myanmar, hampered the functioning of most private and public activities and the relationships between distance and price dispersion have increased. The isolated small farmers depend on biodynamic agriculture practices through cooperatives and soil remineralizers, such as rock dust, to improve the productivity of natural resources systems. Through a study of the rice culture in Myanmar, the article suggests the creation of an institutional environment that supports voluntary forms of cooperatives, developing a culture of independence, self-help and self-governance. As the main contribution this article presents two models: the Culture-Knowledge-Intelligence ( CKI model) and the biodynamic agriculture model based on cultural change, agricultural cooperatives and the remineralizer rock dust to cope with climate change and the various barriers caused by armed conflicts that Myanmar is facing after the military coup, strongly supported by China and Russia. This model is based on Knowledge Management -KM (knowledge creation) and Organizational Intelligence -OI (knowledge application), in particular communities of Practice (KM) and Expert Analysis (OI). The main conclusion is that Myanmar should strengthen ties with India, Laos and Thailand in the area of agriculture, including research about rock dust. Key words: biodynamic agriculture, cooperatives, fixation of nitrogen, knowledge management, Myanmar, organizational intelligence, rice, rock dust,